Dosimetric Study Of 3dcrt And Imrt Techniques Of Localised Prostate Cancer Using Male Pelvic Phantom - Raof, Nursyatina Abdul (2018)
Verification of dose delivery is a basic necessity of quality assurance in radiotherapy treatment. The entire treatment process was replicated with a constructed male pelvic phantom. Intensity modulated radiation therapy (IMRT) and three-dimensional conformal radiotherapy (3DCRT) treatment planning techniques were used for localised prostate cancer treatment using 6MV photon energy. A CT image of male pelvic region from custom made phantom was used to contour the prostate, rectum, bladder and both femoral head. Dose measurements to the target was obtained from the thermoluminescent dosimeters (TLDs) and Gafchromic external beam therapy (EBT3) film while OARs dose measured with TLDs only. Points of interest were identified in phantom for TLDs placement with seventeen (17) holes to the prostate and eighty-three (83) holes distributed among the OARs. A piece of EBT3 film was located at the center of 31 pieces of Perspex where the target was located. Teflon was used to construct both femoral head. The pelvic phantom has been successfully constructed to replicate male pelvic region. All calibrated TLD generated standard deviation in range 0.04 to 0.38. The EBT3 film displayed a linear response (R2=0.9444) from dose range 0 cGy to 400 cGy. Dose delivery to the prostate volume or planning target volume (PTV) measured with TLDs was consistent with 3DCRT planned doses with percentage different from 0.24% to 4.61%. The standard error bar of 5% value on PTV and OARs showed no significant differences between 3DCRT calculation and TLD measurement. The gamma evaluation at PTV using IMRT technique was 95% using EBT3 film. Hence, this new handmade pelvic phantom fulfilled the basic criteria for dosimetric verification to PTV with IMRT technique using EBT3 film and dosimetric verification to PTV and OARs with 3DCRT techniques using TLD.